2021
DOI: 10.2147/idr.s305996
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Analysis Among Genotype Resistance, Phenotype Resistance and Eradication Effect of Helicobacter pylori

Abstract: Background: It has not been fully confirmed whether the detection of Helicobacter pylori resistance gene mutation can replace antibiotic drug sensitivity test to guide the clinical individualized treatment. Therefore, we have studied this aspect and discussed the application value of antibiotic sensitivity gene test. Materials and Methods: The biopsy specimen of gastric mucosa from the patients examined by endoscopy and positive for rapid urease test were collected continuously for histopathological analysis, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 31 publications
(46 reference statements)
0
17
0
5
Order By: Relevance
“…Two concerns for the widespread use of antibiotics are their adverse effects and H. pylori resistance. 117 118 In 2019, one Chinese study investigated H. pylori resistance rates and found that in a treatment-naïve adult group, the resistance rates for metronidazole, clarithromycin, levofloxacin, amoxicillin, rifampicin and tetracycline were 78.4%, 19.0%, 23.3%, 1.2%, 1.7% and 2.3%, respectively. The previously treated adult group had significantly higher resistance rates for metronidazole (99.2%), clarithromycin (58.3%) and levofloxacin (52.3%).…”
Section: Resultsmentioning
confidence: 99%
“…Two concerns for the widespread use of antibiotics are their adverse effects and H. pylori resistance. 117 118 In 2019, one Chinese study investigated H. pylori resistance rates and found that in a treatment-naïve adult group, the resistance rates for metronidazole, clarithromycin, levofloxacin, amoxicillin, rifampicin and tetracycline were 78.4%, 19.0%, 23.3%, 1.2%, 1.7% and 2.3%, respectively. The previously treated adult group had significantly higher resistance rates for metronidazole (99.2%), clarithromycin (58.3%) and levofloxacin (52.3%).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, more rapid, and convenient molecular detection technology is ready. The determination of genotypic resistance using biopsy specimens is more expedient (culture not needed) and speedier, and it is easier to transfer the specimen (Cui et al, 2021) and has a higher success rate compared with traditional susceptibility tests (100.0 versus 92.3% in the present study). Moreover, WGS delivers a more complete picture of resistance determinants present in a clinical isolate than PCR that can only examine a limited number of nucleotide positions (Binh et al, 2015).…”
Section: Discussionmentioning
confidence: 70%
“…Therefore, more rapid, and convenient molecular detection technology is ready. The determination of genotypic resistance using biopsy specimens is more expedient (culture not needed) and speedier, and it is easier to transfer the specimen ( Cui et al, 2021 ) and has a higher success rate compared with traditional susceptibility tests (100.0 versus 92.3% in the present study).…”
Section: Discussionmentioning
confidence: 71%
“…5,[7][8][9][10][11][12][13][14][15][16][17][18] Kháng kiểu gen chiếm 35,9% (95%CI: 28,6 -44,0). Hai nghiên cứu ghi nhận tỉ lệ kháng LVX trên 60% tại Campuchia và Conggo.6 Về kỹ thuật xác định kiểu gen kháng LVX của H. pylori, chỉ có tác giả Maria Teresa Mascellino (2020) sử dụng kỹ thuật PCR để xác định đột biến kiểu gen.9 12 bài báo sử dụng kỹ thuật giải trình tự gen trực tiếp hoặc toàn bộ bộ gen để xác định đột biến trên gen GyrA.…”
unclassified
“…Hai nghiên cứu ghi nhận tỉ lệ kháng LVX trên 60% tại Campuchia và Conggo.6 Về kỹ thuật xác định kiểu gen kháng LVX của H. pylori, chỉ có tác giả Maria Teresa Mascellino (2020) sử dụng kỹ thuật PCR để xác định đột biến kiểu gen.9 12 bài báo sử dụng kỹ thuật giải trình tự gen trực tiếp hoặc toàn bộ bộ gen để xác định đột biến trên gen GyrA. [5][6][7][8][10][11][12][13][14][15][16]18 Và có 4 nghiên cứu là có tiến hành khảo sát đột biến kháng GyrB của H. pylori.8,10,17,18 Đột biến trên gen GyrA được tìm thấy ở 13 bài báo với vị trí đột biến phổ biến ở codon 87 và 91.10,18 Riêng nghiên cứu của tác giả Fangyuan Dong(2015) ghi nhận vị trí thay đổi nucleotide thay vì ghi nhận sự thay đổi amino acid. TCNCYH 160 (12V2) -2022 pylori Mười nghiên cứu đã tiến hành phân tích bằng phép kiểm R để xác định mối liên quan giữa xét nghiệm kiểu hình và xét nghiệm kiểu gen trong việc xác định sự đề kháng LVX của H. pylori trong thời gian 10 năm (2012 -2022), sự khác biệt không có ý nghĩa thống kê.…”
unclassified